Pengembangan Aplikasi Tes Kepribadian Berbasis Intelligent Agent Menggunakan Metode Summary - Azizah Fatmawati; Azhari SN; Nisa RNA (IJCCS (Indonesian Journal of Computing and Cybernetics Systems), 2016)
Saks Sentence Completion Test (SSCT) is one of the projective tests for revealing personality dynamics that is able to show characters of someone toward his or her interpersonal relationship and interpretation to environment. Normally, this kind of test is conducted by psychologists where they have very important and complicated task to interpret respondents' answer test. However, since the advance development of intelligent agent based system, the task that is previously complicated for psychologist now becoming easier. They just need to delegate intelligent agent software to interpret the test result from respondent in order to decide the test result.In this research we developed an intelligent agent software using Java Agent Development Framework (JADE) and BDI as agents architecture with Prometheus method. The application development focuses on how to utilize summary method to generate answer model from SSCT while the psychologists are able to obtain interpretation result immediately.Results showed that the average percentage of successfully identified answers by the model reaches 59.00% while the average percentage of its accuracy is 95.13%. Moreover, by using four agents that are communicating each other psychologists may obtain the test result.